2011
DOI: 10.1088/0022-3727/44/25/253001
|View full text |Cite
|
Sign up to set email alerts
|

Physical processes in EUV sources for microlithography

Abstract: The source is an integral part of an extreme ultraviolet lithography (EUVL) tool. Such a source, as well as the EUVL tool, has to fulfil very high demands both technical and cost oriented. The EUVL tool operates at a wavelength of 13.5 nm, which requires the following new developments. The light production mechanism changes from conventional lamps and lasers to relatively high-temperature emittin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
166
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(169 citation statements)
references
References 71 publications
1
166
0
2
Order By: Relevance
“…The tin spectra provide a useful benchmark for the EUV performance of the galinstan plasmas, under the same range of conditions. The tin spectra show the expected UTA in the range of 13-15 nm as has been reported for both discharge [3][4][5]11 and LPP 12,13 sources. For galinstan, the tin UTA is also observed, but transitions in the range of 11.5-13 nm, due to gallium, and 14-18 nm, due to both gallium and indium, are also present.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…The tin spectra provide a useful benchmark for the EUV performance of the galinstan plasmas, under the same range of conditions. The tin spectra show the expected UTA in the range of 13-15 nm as has been reported for both discharge [3][4][5]11 and LPP 12,13 sources. For galinstan, the tin UTA is also observed, but transitions in the range of 11.5-13 nm, due to gallium, and 14-18 nm, due to both gallium and indium, are also present.…”
supporting
confidence: 80%
“…3 EUV emission from a Z-pinch in a laser-triggered discharge between rotating electrodes coated with liquid tin has been studied previously. 4,5 The liquid metal coating overcomes the problem of electrode erosion, but it is necessary to maintain the tin above its melting temperature of 232 C. The EUV emission spectrum of pure tin plasma, at the appropriate conditions, is relatively narrow-band, with $50% of emission in the 13-15 nm range. For EUV metrology, the source parameters of interest are spectral radiance, wavelength range, and emission uniformity, as well as cost and ease of operation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An important application of drop deformation by laser-pulse impact is found in laserproduced plasma light-sources for extreme ultraviolet (EUV) nanolithography. In these sources a nanosecond laser pulse pre-shapes a falling liquid tin drop into a thin sheet, which is subsequently ionized by a second laser pulse (Mizoguchi et al 2010;Banine et al 2011). To maximize the conversion of liquid tin to plasma a precise control of the drop shape and stability that result from the first laser impact is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…The search for the optimum radiation source at 13.5 nm for extreme ultraviolet lithography (EUVL) has been the subject of intense research activity in recent years [1,2]. These studies have shown that plasmas containing tin, where transitions of the type 4p 6 4d n -4p 5 4d n+1 + 4d n-1 4f overlap in ion stages from Sn 9+ -Sn 13+ to form an unresolved transition array (UTA) centered near 13.5 nm are the strongest emitters at this wavelength.…”
mentioning
confidence: 99%